Lipoprotein X in the Setting of COVID-19–Induced Cholangiopathy: An Unforeseen Event - Hardik Patel; Felix Berglund; Christina C. Lindenmeyer; Nicholas Ruthmann (Annals of Internal Medicine: Clinical Cases)
Elevated low-density lipoprotein cholesterol (LDL-C) is a well-known culprit for atherosclerosis; however, elevated lipoprotein X (LpX), an abnormal lipoprotein as dense as LDL-C, may confound differentiation between true hyperlipidemia and cholestasis-induced hyperlipidemia. We present the case of a 34-year-old man diagnosed with COVID-19–induced cholangiopathy with LpX. Despite treatment with evolocumab and plasmapheresis, the patient had persistent cholestasis and ultimately received a liver transplant, resulting in the resolution of hyperlipidemia. This case highlights the potential association between LpX and COVID-19–induced cholangiopathy, emphasizing the need for further research to better understand the underlying mechanisms and treatment options for this complex disease.